Analisis Dampak Sosial Ekonomi Relokasi Permukiman Kolong Pasupati ke Rusunawa Solokan Jeruk - Sri Damayanti; Setia Rahayu Fadilah; Yusacti Adli Qiyantasari; Teja Aruman (Pusat Riset dan Inovasi Nasional, 2025)
This research discusses the process of relocating residents from informal settlements under the Pasopati Bridge to Simple Rental Flats (Rusunawa) in Solokan Jeruk, Bandung Regency. This relocation is a policy of the Bandung City Government and West Java Provincial Government to organize extreme slum areas and provide adequate housing for low-income people. Using a qualitative approach and literature study, this research analyzes the mechanisms for implementing relocation, the actors involved, and the social and economic impacts experienced by residents after relocation. The research results show that although relocation provides access to more adequate housing and basic facilities, residents face serious challenges in terms of social adaptation, loss of community networks, increased economic burden, and loss of old sources of livelihood. Relocation also causes psychosocial pressure and shifts in the structure of social interactions due to changes in the physical environment and social norms in the flat. This study emphasizes the importance of a participatory approach and comprehensive post-relocation interventions, including economic, social and psychological support, so that relocation is not just a physical transfer, but also a sustainable life transformation for affected residents.